1980
DOI: 10.1021/jm00176a002
|View full text |Cite
|
Sign up to set email alerts
|

.beta.-Adrenergic blocking agents. 19. 1-Phenyl-2-[[(substituted-amido)alkyl]amino]ethanols

Abstract: The synthesis of a series of derivatives of 1-phenyl-2-[[(substituted amido)alkyl]amino]ethanols is described. The compounds were investigated for beta-adrenoceptor blocking properties, and many showed a surprising degree of potency and beta 1-cardioselectivity when tested in vivo in anesthetized cats. The structure-activity relationships shown by this series of compounds are discussed and related to known beta-adrenergic blocking agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1980
1980
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…The IC50 of fentanyl in the MVD was 9.45 ± 4.05 X 10™9 M (n = 11), while that for morphine was 1.94 ± 0.34 X 10-( = 3). Compound 13, which differs from fentanyl (1) only in having an aminocarbonyl group at the 2-position, was 110 and 450 times less potent than fentanyl in the GPI and MVD, respectively. None of the other fentanyl derivatives at a concentration of 1 X 10"6 M (9) .…”
Section: T H Imentioning
confidence: 92%
“…The IC50 of fentanyl in the MVD was 9.45 ± 4.05 X 10™9 M (n = 11), while that for morphine was 1.94 ± 0.34 X 10-( = 3). Compound 13, which differs from fentanyl (1) only in having an aminocarbonyl group at the 2-position, was 110 and 450 times less potent than fentanyl in the GPI and MVD, respectively. None of the other fentanyl derivatives at a concentration of 1 X 10"6 M (9) .…”
Section: T H Imentioning
confidence: 92%
“…1972, 15, 1066. (8) Anderson, T. The results of this study indicated that the number of essential factors is less than the number of primary indices and that the first component was the most important one in determining pharmacological activity. Methods…”
mentioning
confidence: 78%
“…The transformation coefficients were calculated by using principal component analysis. 8 Principal component analysis was used several times in QSAR studies. The investigations involved geometric descriptor indices, substituent constants,9-13 pharmaco- (1) Schnaare, R. S. Drug Des.…”
mentioning
confidence: 99%
See 1 more Smart Citation